Peranan Koperasi dalam Rangka Mensejahterahkan Anggota pada Koperasi UMMAT Mandiri Peureulak - Nuraini; M Djamil HS (Journal of Law and Economics, 2022)
This research explores the role of the UMMAT Mandiri Peureulak Cooperative in the welfare of its members through qualitative and quantitative approaches. By focusing on member characteristics, cooperative programs, and the resulting positive impacts, this research shows that cooperatives have succeeded in creating inclusivity in the local community. The diverse characteristics of members, including age groups, economic backgrounds, and gender, reflect the cooperative's success in embracing all levels of society. Programs such as the provision of goods and services, economic empowerment and social activities have been proven to provide real benefits in improving members' economic and social conditions. Increasing income, developing skills, and improving social welfare are significant positive impacts. In conclusion, the UMMAT Mandiri Peureulak Cooperative plays a key role in forming an inclusive and sustainable local economy.